Associations between redox‐sensitive trace metals and microbial communities in a Proterozoic ocean analogue. Issue 4 (17th March 2020) - Rico, Kathryn I.; Sheldon, Nathan D.; Kinsman‐Costello, Lauren E.
Abstract: Constraints on Precambrian ocean chemistry are dependent upon sediment geochemistry. However, diagenesis and metamorphism can destroy primary biosignatures, making it difficult to consider biology when interpreting geochemical data. Modern analogues for ancient ecosystems can be useful tools for identifying how sediment geochemistry records an active biosphere. The Middle Island Sinkhole (MIS) in Lake Huron is an analogue for shallow Proterozoic waters due to its low oxygen water chemistry and microbial communities that exhibit diverse metabolic functions at the sediment–water interface. This study uses sediment trace metal contents and microbial abundances in MIS sediments and an oxygenated Lake Huron control site (LH) to infer mechanisms for trace metal burial. The adsorption of trace metals to Mn‐oxyhydroxides is a critical burial pathway for metals in oxic LH sediments, but not for the MIS mat and sediments, consistent with conventional understanding of Mn cycling. Micronutrient trace metals (e.g., Zn) are associated with organic matter regardless of oxygen and sulfide availability. Although U and V are conventionally considered to be organically complexed in suboxic and anoxic conditions, U and organic covary in oxic LH sediments, and Mn‐oxyhydroxide cycling dominates V deposition in the anoxic MIS sediments. Significant correlations between Mo and organic matter across all redox regimes have major implications for our interpretations of Mo isotope systematics in the geologic record. Finally, while microbial groups vary between the sampling locales (e.g., the cyanobacteria in the MIS microbial mat are not present in LH sediments), LH and MIS ultimately have similar relationships between microbial assemblages and metal burial, making it difficult to link trace metal burial to microbial metabolisms. Together, these results indicate that bulk sediment trace metal composition does not capture microbiological processes; more robust trace metal geochemistry such as isotopes and speciation may be critical for understanding the intersections between microbiology and sediment geochemistry.